Sosialisasi dan Pelatihan Pengolahan Sampah Organik Rumah Tangga di Desa Batu Jangkih - Yek Zen Mubarok; Doni Anamal; Nurul Hilmi Muliana; Mirza Ainul Islam; Rostihanji Rostihanji; Karina Ayu Septiana; Ninda Luqya Nakadira; Baiq Yuliana; Mia Nurkhofifah; Yogi Septian Hadi; Husmiati Husmiati; Muhammad Hilmi; Saipul Hamdi (Rengganis Jurnal Pengabdian Masyarakat, 2022)
Problems caused by indiscriminate and improperly disposed waste can cause big problems for the environment and society. This article specifically investigates waste in Batu Jangkih village, where there are still people littering and lack of knowledge about how to use waste properly. One solution to the waste problem in Batu Jangkih Village is to use household organic waste to be processed into compost. This activity is a service to the community in Batu Jangkih village. The purpose of this service activity is to provide information and additional knowledge to the community through socialization and training in order to increase public awareness of the environment and to utilize and process organic waste properly. The method of implementing service activities is carried out in 3 stages, namely identification of problems related to waste, preparation for implementation of activities, and implementation of activities. The result of this activity is the addition of knowledge and skills of the people of Batu Jangkih Village in the utilization and processing of household organic waste so that it can reduce waste that is littered outside the house and into illegal landfills that have the potential to pollute the environment.